Internalisasi Nilai Karakter Disiplin dan Tanggung Jawab dalam Pembelajaran IPS Terpadu - Rachmawati Fanan, Aufa; Soraya, Siti Zazak (Institut Agama Islam Negeri Ponorogo, 2024)
The research aimed to discover methods and the factors that help and hinder the development of discipline and student accountability from developing character values of discipline and student accountability in the integrated social studies learning process at SMP Ma'arif 2 Ponorogo. This study employed a qualitative research method. Observation, interviews, and documentation were employed to obtain data for this study. The analysis technique employed in this study is interactive data analysis. The result of study showed that (1) the instillation of discipline-related character values is well implemented through a) lesson plans integrated with character education of discipline and responsibility, b) exemplary teacher, c) habituation. (2) The instillation of the character of student responsibility is going well, as evidenced by: a) lesson plan that is integrated with the character of responsibility; b) teacher's example; and c) habituation. (3) Environmental variables and teachers assist the instillation of student discipline characters. Still, student and parent awareness impede establishing discipline. (4) The school and the environment are supporting factors for instilling the character of student responsibility. In contrast, (a) teachers and (b) students' laziness are factors that impede the development of the character of student responsibility.